2015
DOI: 10.1016/j.actatropica.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Subtle to severe hepatobiliary morbidity in Opisthorchis viverrini endemic settings in southern Laos

Abstract: Evidence of severe hepatobiliary morbidity associated with Opisthorchis viverrini liver fluke infection including cholangiocarcinoma (CCA) is scarce in Laos although O. viverrini infection is highly prevalent. We assessed hepatobiliary morbidity using abdominal ultrasonography (US) in O. viverrini adult patients in Saravan province, Southern Laos. A random sample of 431 O. viverrini patients from 10 villages underwent abdominal US. Mild, moderate and markedly advanced periductal fibrosis was diagnosed in 7.0%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…In Southeast Asia, more than 90 million people are at risk of infection, and at least 10 million people are estimated to be infected with Ov (Andrews et al, 2008; Sripa et al, 2010; Sithithaworn et al, 2012a). In Lao PDR, high endemicity and prevalence rates to up to 90% in certain communities have been observed (Rim et al, 2003; Sayasone et al, 2009; Ayé Soukhathammavong et al, 2015). Reliable national data from Cambodia and southern Vietnam are lacking but local prevalence estimates can be high in each of these countries (Sithithaworn et al 2012a).…”
Section: Medical and Public Health Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In Southeast Asia, more than 90 million people are at risk of infection, and at least 10 million people are estimated to be infected with Ov (Andrews et al, 2008; Sripa et al, 2010; Sithithaworn et al, 2012a). In Lao PDR, high endemicity and prevalence rates to up to 90% in certain communities have been observed (Rim et al, 2003; Sayasone et al, 2009; Ayé Soukhathammavong et al, 2015). Reliable national data from Cambodia and southern Vietnam are lacking but local prevalence estimates can be high in each of these countries (Sithithaworn et al 2012a).…”
Section: Medical and Public Health Significancementioning
confidence: 99%
“…While no studies to our knowledge have formally investigated resistance to PZQ, or reported evidence for its occurrence in the case of Ov (but see Ayé Soukhathammavong et al 2015), resistance to PZQ in schistosomes infection treatment has been relatively thoroughly investigated. To date, there is no evidence to suggest that schistosomes have already developed and/or established resistance to PZQ under field conditions, even within China where praziquantel-based chemotherapy has reached more than 50 million people since 1992 (Doenhoff et al, 2002; Liang et al, 2011; Seto et al, 2011; Wang et al, 2010; 2012).…”
Section: Evolutionary Concepts In Predicting and Assessing The Impmentioning
confidence: 99%
“…«крышечкой» и определенные размеры -22-32 × 10-19 мкм [20]. При малоинтенсивной инвазии рекомендуют использовать провокационную пробу -исследование дуоденального содержимого и фекалий через 1-2 дня после однократного приема 1 таблетки празиквантела (600 мг): часть взрослых особей паразитов погибает или обездвиживается и может быть найдена в кале или желчи вместе с яйцами [21].…”
Section: диагностика описторхозаunclassified
“…Метод нативного мазкасамый простой, но его эффективность при средней и высокой интенсивности инвазии составляет от 44% до 63% и еще меньше при низкой интенсивности инвазии. Более информативен метод Като -метод толстого мазка под целлофаном [21]. Толстый мазок представляет собой слой неразбавленных фекалий на предметном стекле, спрессованный под листком тонкого гигроскопичного целлофана, предварительно пропитанного глицерином.…”
Section: диагностика описторхозаunclassified
“…The International Agency for Research on Cancer of the World Health Organization classifies infection with the liver flukes O. viverrini and Clonorchis sinensis as well as H. pylori as Group 1 carcinogens [6]. In northern and northeastern Thailand and Laos, opisthorchiasis is the major documented risk factor for CCA [6][7][8][9]. Given the elevated prevalence of CCA in this region where infection with liver fluke prevails, and given evidence of linkages between infection by Helicobacter during opisthorchiasis, these two biological carcinogens together may orchestrate the pathogenesis of opisthorchiasis and bile duct cancer.…”
Section: Introductionmentioning
confidence: 99%